Carers of forensic mental health in-patients: What factors influence their satisfaction with services?. (December 2013) - Macinnes, Douglas; Beer, Dominic; Reynolds, Kelly; Kinane, Catherine
<x xml:space="preserve">Abstract</x> Background Families are the main caring resource for service users with severe mental health problems. There has been limited work examining the needs of carers of people using forensic mental health services. Aims This study aimed to gain an understanding of carers satisfaction with services in forensic mental health inpatient settings. Method A survey design was used with 63 carers interviewed by telephone using a structured interview schedule. The data were analysed both qualitatively and quantitatively. Results Most carers were pleased with the service provided although some negative views were expressed with specific types of contact. Giving appropriate information to carers was strongly associated with satisfaction with the service being provided. Conclusions Carer satisfaction with forensic mental health services is likely to be higher with services that address carers' information needs. New ways of providing this information may offer greater opportunities for working with carers.